Pico malformado en una Catita Serrana Chica (Psilopsiagon aurifrons) silvestre - Quiroga, Oscar B.; Aveldaño, Sebastián; Mamani, Julio C.; Moreno Ten, Thania (Nuestras Aves, 2016)
Este artículo no cuenta con un resumen.